Genetic risk variants for childhood nephrotic syndrome and corticosteroid response - Cason, Rachel K.; Chambers, Eileen; Tu, Tiffany; Chryst-Stangl, Megan; Huggins, Kinsie; Lane, Brandon M.; Ochoa, Alejandro; Jackson, Annette M.; Gbadegesin, Rasheed A. (Frontiers in Pediatrics, 2023)
The etiology of most cases of nephrotic syndrome (NS) remains unknown, therefore patients are phenotypically categorized based on response to corticosteroid therapy as steroid sensitive NS (SSNS), or steroid resistant NS (SRNS). Genetic risk factors have been identified for SSNS from unbiased genome-wide association studies (GWAS), however it is unclear if these loci are disease risk loci in other forms of NS such as SRNS. Additionally, it remains unknown if these risk loci are associated with response to therapy. Thus, we investigated the association between SSNS risk loci and therapy response in a large, multi-race cohort of children along the entire spectrum of childhood-onset NS. Methods: We enrolled 1000 patients with childhood-onset NS comprised of SSNS and SRNS. Genotyping was done using TaqMan and Direct Sanger Sequencing for 9 previously reported childhood SSNS risk loci. We compared the allele frequencies (AF) and variant burden between NS vs. controls and SRNS vs. SSNS. Results: All 9 risk loci were associated with NS compared with healthy controls (p=3.5x10 -3 to <2.2x10 -16 ). Variant burden greater than 7 was associated with risk of SRNS (OR 7.4, 95% CI 4.6 -12.0, p=8.2x10 -16 ). Conclusion: Our study showed that genetic risk loci for childhood SSNS are associated with pattern of therapy response, may help predict disease outcome, and set the stage for individualized treatment of NS.